Lithium-ion batteries and electronic devices

By introducing chloroprene into the negative electrode active material layer of the lithium-ion battery, the problem of vulnerability to the negative electrode structure during charging and discharging is solved, and the circulation performance and structural stability of the lithium-ion battery are significantly improved.

CN112952094BActive Publication Date: 2025-03-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110103910.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-26
Publication Date
2025-03-25
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

The negative electrode structure of lithium-ion batteries is easily damaged during charging and discharging, affecting the cycling performance, and the prior art is difficult to improve the kinetic performance while maintaining structural stability.

Method used

Neoprene is introduced into the negative electrode active material layer of lithium-ion batteries. By adding chloroprene to the binder, the structural stability and tensile ability of the negative electrode are improved, thereby preventing the destruction of the bonding interface during charging and discharging.

Benefits of technology

By using chloroprene, the circulation performance of lithium-ion batteries is significantly improved, the probability of bonding interface is reduced, and the overall structural stability of the negative electrode is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002917099870000101
    Figure BDA0002917099870000101
  • Figure BDA0002917099870000111
    Figure BDA0002917099870000111
Patent Text Reader

Abstract

In the embodiment of the present application, a lithium ion battery and an electronic device are provided, wherein the lithium ion battery comprises a negative electrode, the negative electrode comprises a current collector and an active material layer, and the active material layer comprises chloroprene rubber. The chloroprene rubber with excellent tensile ability can provide stress dissipation points inside the negative electrode, thereby preventing the bond interface from being damaged during the charge and discharge process, thereby improving the structural stability of the negative electrode during the charge and discharge process, and further improving the cycle performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a lithium ion battery and an electronic device. Background Art

[0002] In recent years, with the rapid development of electronic products and electric vehicles, the requirements for the cycle performance of lithium-ion batteries have become increasingly higher. However, during the charge and discharge process, the negative electrode structure is often destroyed due to the volume change of the negative electrode active material, which affects the cycle performance of the lithium-ion battery. Therefore, improving the structural stability of the negative electrode during the charge and discharge process, thereby improving the cycle performance of the lithium-ion battery, is an urgent problem to be solved in this field. Summary of the invention

[0003] The present application provides a lithium ion battery, comprising a negative electrode, wherein the negative electrode comprises a current collector and an active material layer, and the active material layer comprises chloroprene rubber.

[0004] In some embodiments, the active material layer further includes a binder, and the chloroprene rubber is present in the binder.

[0005] In some embodiments, the binder further comprises: a water-soluble polymer. The water-soluble polymer comprises: at least one of polyacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, xanthan gum, polyvinyl alcohol or polyvinyl pyrrolidone.

[0006] In some embodiments, the lithium ion battery satisfies at least one of the following conditions (a) to (d):

[0007] (a) The average particle size Dv50 of chloroprene rubber satisfies: 10nm≤Dv50≤400nm;

[0008] (b) The elastic modulus E1 of chloroprene rubber satisfies: 0.5MPa≤E1≤30MPa;

[0009] (c) The elongation at break of the chloroprene rubber film δ satisfies: 1500%≤δ≤8000%;

[0010] (d) The mass proportion X of the chloroprene rubber in the adhesive satisfies: 5%≤X≤60%.

[0011] In some embodiments, the lithium ion battery satisfies at least one of the following conditions (a) to (d):

[0012] (a) The average particle size Dv50 of chloroprene rubber satisfies: 50nm≤Dv50≤300nm;

[0013] (b) The elastic modulus E1 of chloroprene rubber satisfies: 1MPa≤E1≤20MPa;

[0014] (c) The elongation at break of the chloroprene rubber film δ satisfies: 1500%≤δ≤4000%;

[0015] (d) The mass proportion X of the chloroprene rubber in the adhesive satisfies: 10%≤X≤50%.

[0016] In some embodiments, the mass proportion Y of the water-soluble polymer in the binder satisfies: 40%<Y<95%.

[0017] In some embodiments, the binder further includes inorganic particles, and the inorganic particles include at least one of SiO2, TiO2, Al2O3, CaCO3, MgO, BaSO4, CaSO4, or carbon black.

[0018] In some embodiments, the inorganic particles have a Dv50 ≤ 100 nm.

[0019] In some embodiments, the mass content ratio of chloroprene rubber, water-soluble polymer and inorganic particles in the adhesive is (5% to 60%): (40% to 95%): (0% to 20%).

[0020] In some embodiments, the elastic modulus E2 of the binder satisfies: 5 GPa≤E2≤30 GPa.

[0021] The present application also provides an electronic device, comprising the lithium-ion battery provided in the present application.

[0022] The lithium-ion battery and electronic device provided in the embodiment of the present application include a negative electrode, the negative electrode includes a current collector and an active material layer, and the active material layer includes chloroprene rubber. The chloroprene rubber with excellent tensile ability can provide stress dissipation points inside the negative electrode, thereby preventing the bond interface from being damaged during the charge and discharge process, thereby improving the structural stability of the negative electrode during the charge and discharge process, and further improving the cycle performance of the lithium-ion battery. DETAILED DESCRIPTION

[0023] The embodiments of the present application will be described in more detail below. Although some embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be interpreted as being limited to the embodiments set forth herein, but rather these embodiments are provided to provide a more thorough and complete understanding of the present application. It should be understood that the embodiments of the present application are only for exemplary purposes and are not intended to limit the scope of protection of the present application.

[0024] The negative electrode of lithium-ion batteries expands during charging. Excessive expansion can damage the negative electrode bonding interface and reduce cycle performance. Increasing the amount of binder or using a binder with a higher modulus can better maintain the negative electrode structure, but this often deteriorates the dynamic performance or increases the brittleness of the negative electrode, making it easier to cause bond interface damage. Adding styrene-butadiene rubber or styrene-propylene rubber can often alleviate interface damage and thus improve cycle performance, but the tensile properties of styrene-butadiene rubber and styrene-propylene rubber are insufficient, and they have a significant weakening effect on the elastic modulus of the adhesive layer, making it difficult to maintain the overall structure of the negative electrode.

[0025] The present application provides a lithium-ion battery, including a negative electrode, the negative electrode including a current collector and an active material layer, and the active material layer including chloroprene rubber. In some embodiments, since the active material layer of the negative electrode contains chloroprene rubber, during the charging and discharging process of the lithium-ion battery, the chloroprene rubber with excellent tensile ability in the active material layer can provide stress dissipation points inside the negative electrode, thereby preventing the bonding interface from being damaged during the charging and discharging process, improving the structural stability of the negative electrode during the charging and discharging process, and further improving the cycle performance of the lithium-ion battery. In the present application, by using chloroprene rubber with excellent tensile properties in the active material layer, the probability of the bonding interface being damaged is greatly reduced, thereby improving the cycle performance of the lithium-ion battery.

[0026] In some embodiments of the present application, the active material layer includes a binder, and chloroprene rubber is present in the binder. In some embodiments, the active material layer is bonded to the current collector via the binder, and by using chloroprene rubber in the binder, the stability of the bonding interface can be improved to prevent the bonding interface from being damaged during the charge and discharge process.

[0027] In some embodiments of the present application, the binder further comprises: a water-soluble polymer; the water-soluble polymer comprises: at least one of polyacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, xanthan gum, polyvinyl alcohol or polyvinyl pyrrolidone. In some embodiments, the water-soluble polymer can play a thickening role and can absorb the electrolyte as a carrier of the electrolyte, thereby facilitating the transmission of lithium ions.

[0028] In some embodiments of the present application, the average particle size Dv50 of chloroprene rubber satisfies: 10nm≤Dv50≤400nm. In some embodiments, when the Dv50 of chloroprene rubber is greater than 400nm, the area of ​​the stress dissipation point will be too large, and the excessively large area of ​​the stress dissipation region is not conducive to maintaining the stability of the negative electrode structure. When the Dv50 of chloroprene rubber is less than 10nm, the stress concentration may be caused by the small area of ​​the stress dissipation region, resulting in the chloroprene rubber breaking. Therefore, in some embodiments, the average particle size Dv50 of chloroprene rubber satisfies: 10nm≤Dv50≤400nm. In some embodiments, the average particle size Dv50 of chloroprene rubber satisfies: 50nm≤Dv50≤300nm, at which time the performance of the lithium-ion battery is better.

[0029] In some embodiments of the present application, the elastic modulus E1 of chloroprene rubber satisfies: 0.5MPa≤E1≤30MPa. In some embodiments, when the elastic modulus E1 of chloroprene rubber is less than 0.5MPa, it will be difficult to prepare, and may result in insufficient binding force for the negative electrode active material on the negative electrode, resulting in an unstable negative electrode structure. When the elastic modulus E1 of chloroprene rubber is not less than 0.5MPa, the smaller the elastic modulus E1 of chloroprene rubber, the better the stress dissipation effect. When the elastic modulus E1 of chloroprene rubber is greater than 30MPa, it may be detrimental to maintaining the stability of the bonding interface. In some embodiments, the elastic modulus E1 of chloroprene rubber satisfies: 1MPa≤E1≤20MPa, at which time the negative electrode of the lithium-ion battery is more stable and has better performance.

[0030] In some embodiments of the present application, the elongation at break δ of the chloroprene film satisfies: 1500%≤δ≤8000%. In some embodiments, when the elongation at break δ of the chloroprene film is not greater than 8000%, the binder layer distributed in the negative electrode can better maintain the overall structure of the negative electrode and ensure the normal cycle of the lithium-ion battery; when the elongation at break δ of the chloroprene film is greater than 8000%, during the cycle of the lithium-ion battery, some active substances are not effectively bound, resulting in the destruction of the conductive network and loss of reaction activity, thereby causing capacity decay. When the elongation at break δ of the chloroprene film is not less than 1500%, the chloroprene is not easy to break, and can maintain the stability of the bonding interface of the negative electrode for a long time, thereby improving the cycle performance; when the elongation at break δ of the chloroprene film is less than 1500%, the chloroprene may break during the cycle of the lithium-ion battery, resulting in the inability to maintain the capacity retention rate of the lithium-ion battery during the cycle, resulting in a decrease in the cycle performance. In some embodiments, 1500%≤δ≤4000%, in which case the chloroprene rubber can better maintain the overall structure of the negative electrode and is not easy to break.

[0031] In some embodiments of the present application, the mass proportion X of chloroprene rubber in the binder satisfies: 5%≤X≤60%. In some embodiments, when the mass proportion of chloroprene rubber in the binder is less than 5%, the improvement of the cycle performance of the lithium-ion battery may not be obvious; when the mass proportion of chloroprene rubber in the binder is greater than 60%, the impedance of the negative electrode may increase due to the poor conductivity of chloroprene rubber. In some embodiments, 10%≤X≤50%, at this time, chloroprene rubber can better improve the cycle performance of the lithium-ion battery without significantly affecting the impedance.

[0032] In some embodiments of the present application, the mass proportion Y of the water-soluble polymer in the binder satisfies: 40%<Y<95%. In some embodiments, when the mass proportion of the water-soluble polymer is too low, it is not conducive to the conductivity of the negative electrode. When the mass proportion of the water-soluble polymer is too high, the chloroprene rubber content is insufficient, which may lead to insignificant improvement in the cycle performance of the lithium-ion battery.

[0033] In some embodiments, the binder further comprises inorganic particles, and the inorganic particles comprise at least one of SiO2, TiO2, Al2O3, CaCO3, MgO, BaSO4, CaSO4 or carbon black. In some embodiments, the inorganic particles play a reinforcing role in the binder, and the inorganic particles can improve the structural stability of the binder.

[0034] In some embodiments, the Dv50 of the inorganic particles is ≤100 nm. In some embodiments, when the Dv50 of the inorganic particles is too large, the continuity of the binder will be affected, which is not conducive to maintaining the overall structural stability of the negative electrode.

[0035] In some embodiments, the mass content ratio of chloroprene rubber, water-soluble polymer and inorganic particles in the adhesive is (5% to 60%): (40% to 95%): (0% to 20%).

[0036] In some embodiments, the elastic modulus E2 of the binder satisfies: 5GPa≤E2≤30GPa. In some embodiments, when the elastic modulus E2 of the binder is less than 5GPa, the binding effect of the binder on the negative electrode is poor, which may cause the negative electrode to expand during the cycle of the lithium-ion battery, resulting in accelerated capacity decay during the cycle. In some embodiments, the elastic modulus E2 of the binder is greater than 30GPa, which may be unfavorable for maintaining the stability of the negative electrode bonding interface. In some embodiments, the elastic modulus of the binder is 5GPa to 15GPa.

[0037] In some embodiments, the active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, hard carbon, silicon, silicon carbon, or silicon monoxide.

[0038] In some embodiments, the negative electrode active material is a carbon material, and when the lithium ion battery is cycled 400 times at 1.5C / 1C, the capacity retention rate of the lithium ion battery is not less than 92%; in some embodiments, the negative electrode active material is a silicon-containing material, and when the lithium ion battery is cycled 400 times at 0.5C / 0.5C, the capacity retention rate of the lithium ion battery is not less than 92%.

[0039] In some embodiments, the current collector of the negative electrode can be at least one of copper foil, nickel foil or carbon-based current collector. In some embodiments, the compaction density of the active material layer of the negative electrode can be 1.0 g / cm 3 Up to 1.9g / cm 3 If the compaction density of the active material layer is too small, the volume energy density of the lithium-ion battery will be lost. If the compaction density of the active material layer is too large, it will be difficult for lithium ions to pass through, polarization will increase, the electrochemical performance will be affected, and lithium will be easily precipitated during the charging process of the lithium-ion battery.

[0040] In some embodiments, the active material layer of the negative electrode may further include a conductive agent, and the conductive agent in the active material layer of the negative electrode may include at least one of conductive carbon black, Ketjen black, flake graphite, graphene, carbon nanotubes, or carbon fibers.

[0041] In some embodiments, the lithium-ion battery further comprises: a positive electrode and a separator, wherein the separator is disposed between the positive electrode and the negative electrode. The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer is disposed on one side or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may be Al foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 200 μm. In some embodiments, the positive electrode active material layer may be coated only on a partial area of ​​the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer may be 10 μm to 500 μm. In some embodiments, the positive electrode active material layer may further comprise a conductive agent. In some embodiments, the conductive agent in the positive electrode active material layer may comprise at least one of conductive carbon black, Ketjen black, flake graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, the positive electrode active material layer has a positive electrode active material, and the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode active material layer may be 70 to 98:1 to 15:1 to 15. It should be understood that the above description is only an example, and the active material layer of the positive electrode may adopt any other suitable material, thickness and mass ratio.

[0042] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 500 μm.

[0043] In some embodiments, the surface of the isolation membrane may further include a porous layer, which is disposed on at least one surface of the substrate of the isolation membrane, and the porous layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate.

[0044] In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The adhesive of the porous layer is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece.

[0045] In some embodiments of the present application, the lithium-ion battery is a wound lithium-ion battery or a stacked lithium-ion battery.

[0046] In some embodiments, the lithium ion battery may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.

[0047] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0048] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0049] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0050] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0051] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0052] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0053] Embodiments of the present application also provide electronic devices including the above-mentioned lithium-ion batteries. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In certain embodiments, the electronic device can include, but is not limited to, notebook computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, and large household batteries, etc.

[0054] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example. In order to facilitate the explanation of the technical effect of the present application, the difference between each embodiment and comparative example is only that the binder in the negative electrode is different.

[0055] The embodiments of the present application relate to a lithium-ion battery, in which the negative electrode active material layer includes chloroprene rubber. The embodiments herein are described by taking the addition of chloroprene rubber to a binder as an example, but chloroprene rubber can also be added alone as an additive to the negative electrode active material slurry. The following embodiments are only used for illustrative purposes and should not limit the scope of protection of the present application.

[0056] Example 1

[0057] (1) Preparation of positive electrode

[0058] The positive electrode active materials lithium cobalt oxide (LiCoO2), Super P, and polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under a vacuum mixer until the system is uniform to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72wt%; the positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil; the aluminum foil is dried at 85°C, and then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode sheet.

[0059] (2) Negative electrode preparation

[0060] The negative electrode active material is a mixture of artificial graphite and silicon. The negative electrode active material, Super P, a binder, and styrene-butadiene rubber (SBR) are mixed in a weight ratio of 96.2:1.5:0.5:1.8, and deionized water is added. A negative electrode slurry is obtained under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 54wt%; the negative electrode slurry is uniformly coated on the negative electrode current collector copper foil; the copper foil is dried at 85°C, and then after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet.

[0061] (3) Preparation of electrolyte

[0062] In a dry argon atmosphere glove box, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0063] (4) Preparation of isolation membrane

[0064] 8 μm thick polyethylene (PE) was selected as the isolation membrane.

[0065] (5) Preparation of lithium-ion batteries

[0066] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain a bare battery cell; after welding the pole ears, the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation (charging at a constant current of 0.02C to 3.5V, and then charging at a constant current of 0.1C to 3.9V), shaping, capacity testing and other processes, a soft-pack lithium-ion battery (thickness 3.3mm, width 39mm, length 96mm) is obtained.

[0067] In each embodiment and comparative example, the adhesive parameters are changed based on the steps of embodiment 1. The specific changed parameters are shown in Table 1 below.

[0068] The test methods for various parameters of this application are described below.

[0069] Elastic modulus test:

[0070] Instrument: DMA850; Constant strain mode test - 60μm thick, 6mm wide film (60℃ drying film), test steps: the sample is fixed between the upper and lower clamps, the upper clamp is fixed, the lower clamp applies a sinusoidal strain to the sample, and the sinusoidal stress of the test material response is tested.

[0071] Elastic modulus = (stress / strain) cosδ

[0072] Elongation at break test:

[0073] Instrument: Universal testing machine; Prepare 2cm wide and 2mm thick film (drying at 60℃), and test in tensile mode. Test steps: Fix the initial distance between the upper and lower clamps L0, that is, the initial length of the sample is 40mm, and stretch the upper clamp at a constant rate of 50mm / min until the sample breaks, at which time the distance between the upper and lower clamps is L1;

[0074] Elongation at break = (L1-L0) / L0.

[0075] Particle size test:

[0076] Dv50 represents the particle size at which the volume accumulation reaches 50% from the smaller particle size side in the volume-based particle size distribution, and the unit is μm.

[0077] The volume particle size distribution can be measured using a laser diffraction particle size distribution meter (Mastersizer 3000) according to the particle size distribution laser diffraction method (specifically refer to GB / T19077-2016), and the volume distribution of the average particle size is represented by the median value Dv50.

[0078] Cycle test:

[0079] The formed lithium-ion battery was charged at 1.0C constant current to 4.2V at 25°C, then charged at 0.7C constant current to 4.35V, then charged at 0.5C constant current to 4.45V, and then charged at constant voltage to a current of 0.05C. After standing for 5 minutes, it was discharged at 0.5C to 3.0V. This charge and discharge cycle was repeated 400 times; the first discharge capacity was recorded as D0, and the 400th cycle discharge capacity was recorded as D1;

[0080] 400 cycle capacity retention rate (%) = D1 / D0×100%.

[0081] The binders used in the negative electrodes in Examples 1 to 33 and Comparative Examples 1 to 4 and the performance test results are shown in Table 1.

[0082] Table 1

[0083]

[0084]

[0085] Note: PAA is polyacrylic acid; PAA-Li is lithium polyacrylate; PAA-Na is sodium polyacrylate; CMC-Na is sodium carboxymethyl cellulose; CMC-Li is lithium carboxymethyl cellulose; PVA is polyvinyl alcohol; PVP is polyvinyl pyrrolidone. The "percentages" in Table 1 are all mass percentages in the binder.

[0086] By comparing Examples 1 to 33 and Comparative Examples 3 and 4, it can be seen that the 400 cycle capacity retention rates of Examples 1 to 33 are higher than those of Comparative Examples 3 and 4. This is because chloroprene rubber is added to the binder of Examples 1 to 33. The chloroprene rubber provides stress dissipation points inside the negative electrode during the cycle, avoiding damage to the bonding interface during the cycle, thereby improving the cycle performance of the lithium-ion battery. Therefore, in some embodiments, the binder for the negative electrode is specified to include chloroprene rubber.

[0087] By comparing Examples 1 to 9, it can be seen that the 400 cycle capacity retention rates of Examples 2 to 9 are all higher than those of Example 1. This is because the binders in Examples 2 to 9 include inorganic particles. The presence of the inorganic particles enhances the binder, thereby improving the cycle performance. Therefore, in some embodiments, the binder is specified to include inorganic particles.

[0088] By comparing Examples 10 to 15, it can be seen that when the elastic modulus of the binder is not less than 5 GPa, the 400 cycle capacity of the lithium-ion battery is relatively high. This may be because when the elastic modulus of the binder is not less than 5 GPa, the binder has a better binding effect on the negative electrode, which can inhibit the expansion of the negative electrode, thereby improving the cycle performance of the lithium-ion battery. Therefore, in some embodiments, the elastic modulus of the binder is limited to not less than 5 GPa.

[0089] By comparing Examples 16 to 21 with Comparative Example 2, it can be seen that the 400 cycle capacity retention rates of Examples 16 to 21 are better than those of Comparative Example 2. This is because the particle size of the chloroprene rubber in Comparative Example 2 is 600 nm. Since the particle size of the chloroprene rubber is too large, the area of ​​the stress dissipation point is too large. When the area of ​​the stress dissipation point is too large, it is not conducive to maintaining the overall structural stability of the negative electrode, resulting in a decrease in the cycle performance. Therefore, in some embodiments, the Dv50 of the chloroprene rubber is limited to no more than 400 nm.

[0090] By comparing Examples 22 to 27 with Comparative Example 1, it can be seen that the 400 cycle capacity retention rates of Examples 22 to 27 are all higher than those of Comparative Example 1. This may be because the size of the inorganic particles in Comparative Example 1 is 300nm. Since the size of the inorganic particles is too large, the continuity of the binder is affected, which is not conducive to maintaining the structure of the negative electrode. Therefore, in some embodiments, the Dv50 of the inorganic particles is limited to ≤100nm.

[0091] By comparing Examples 28 to 33, it can be seen that the 400 cycle capacity retention rates of Examples 28 to 33 are all relatively high. It can be seen that when the elastic modulus of the chloroprene rubber is not greater than 30 MPa and the elongation at break of the film is not less than 1500%, the cycle performance of the lithium-ion battery is relatively good. Therefore, in some embodiments, the elastic modulus of the chloroprene rubber is limited to ≤30 MPa, and the elongation at break of the chloroprene rubber film is ≥1500%.

[0092] Although the subject matter has been described in language specific to structural features and / or methodological logical actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or actions described above. On the contrary, the specific features and actions described above are merely example forms of implementing the claims.

Claims

1. A lithium ion battery, comprising a negative electrode, wherein the negative electrode comprises a current collector and an active material layer, characterized in that: The active material layer includes chloroprene rubber; The active material layer further comprises a binder, and the chloroprene rubber is present in the binder; The binder further comprises: a water-soluble polymer; the water-soluble polymer comprises: at least one of polyacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, xanthan gum, polyvinyl alcohol or polyvinyl pyrrolidone; The binder further comprises inorganic particles, wherein the inorganic particles comprise at least one of TiO2, Al2O3, CaCO3, MgO, BaSO4 or CaSO4; The mass content ratio of the chloroprene rubber, the water-soluble polymer and the inorganic particles in the binder is (10% to 50%): (40% to 95%): (5% to 20%); The elastic modulus E2 of the adhesive satisfies: 9GPa≤E2≤30GPa.

2. The lithium-ion battery according to claim 1, characterized in that Satisfy at least one of the following conditions (a) to (c): (a) the average particle size Dv50 of the chloroprene rubber satisfies: 10nm≤Dv50≤400nm; (b) the elastic modulus E1 of the chloroprene rubber satisfies: 0.5MPa≤E1≤30MPa; (c) The elongation at break δ of the chloroprene rubber film satisfies: 1500%≤δ≤8000%.

3. The lithium-ion battery according to claim 1, characterized in that Satisfy at least one of the following conditions (a) to (c): (a) the average particle size Dv50 of the chloroprene rubber satisfies: 50nm≤Dv50≤300nm; (b) the elastic modulus E1 of the chloroprene rubber satisfies: 1MPa≤E1≤20MPa; (c) The elongation at break δ of the chloroprene rubber film satisfies: 1500%≤δ≤4000%.

4. The lithium-ion battery according to claim 1, characterized in that: The mass proportion Y of the water-soluble polymer in the binder satisfies: 40%<Y<95%.

5. The lithium-ion battery according to claim 1, characterized in that: The Dv50 of the inorganic particles is ≤100nm.

6. An electronic device, characterized in that: Comprising a lithium ion battery as claimed in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Lithium ion battery cathode and lithium ion battery

    CN103326027A

  • Negative electrode for secondary cell, secondary cell, slurry composition, and manufacturing method

    CN104272508A

  • Battery cell and energy storage device

    CN107516721A

  • An anode sheet and a lithium ion battery

    CN107546363A

  • Negative plate, negative slurry, preparation method of negative slurry and battery

    CN111554880A